Unequal freedom: how race and gender shaped American citizenship and labor - Glenn, Evelyn Nakano (Harvard University Press, 2002)
The inequalities that persist in America have deep historical roots. Evelyn Nakano Glenn untangles this complex history in a unique comparative regional study from the end of Reconstruction to the eve of World War II. During this era the country experienced enormous social and economic changes with the abolition of slavery, rapid territorial expansion, and massive immigration, and struggled over the meaning of free labor and the essence of citizenship as people who previously had been excluded sought the promise of economic freedom and full political rights.After a lucid overview of the concepts of the free worker and the independent citizen at the national level, Glenn vividly details how race and gender issues framed the struggle over labor and citizenship rights at the local level between blacks and whites in the South, Mexicans and Anglos in the Southwest, and Asians and haoles (the white planter class) in Hawaii. She illuminates the complex interplay of local and national forces in American society and provides a dynamic view of how labor and citizenship were defined, enforced, and contested in a formative era for white-nonwhite relations in America.
Le chapitre « Citizenship: Universalism and Exclusion » a été donné en lecture au cours POL4212.
Keywords: 1800-1899; 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; amériques; approches et analyses; cours; discipline; droits des femmes*; droits des personnes; histoire et politique; intersectionnalité; inégalités; pol4212; premier cycle; périodes historiques; racisme; racisme systémique; régions géographiques; sexisme; systèmes d'oppressions; thématiques; états-unis; études critiques de la race; études de genres

Loving internationalism: The emotion culture of transnational women's organizations, 1888-1945 - Taylor, Verta; Rupp, Leila (Mobilization: An International Quarterly, 2002)
Keywords: 1800-1899; 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; allemagne; amériques; angleterre; discipline; droits des femmes*; europe; femmes* trans; france; militance; pays-bas; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sociologie; thématiques; émotions; états-unis

Parlementaires canadiens et le suffrage feminin: un apercu des debats - Lamoureux, Diane; Michaud, Jacinthe (Canadian Journal of Political Science)
Les femmes canadiennes ont acquis le droit de vote en 1918. Soit. Cela signifie-t-il pour autant que les parlementaires canadiens se sont ralliés, à cette occasion, au principe de l'égalité entre les sexes? A travers l'analyse des débats parlementaires, on peut aisément constater que les enjeux étaient constamment masqués, que d'autres principes étaient à l'oeuvre et que le débat de fond a été soigneusement évité. Ceci se vérifie autant en 1885 et 1918, où il y a quand même eu débat, qu'en 1898 et 1917, où l'on jouait à cache-cache avec la question. Quelles conséquences cela revêt-il en ce qui concerne la citoyenneté des femmes?
Keywords: 1800-1899; 1900-1909; 1900-1999; 1910-1919; amériques; approches et analyses; canada; cours; discipline; droit de vote; droits des femmes*; histoire et politique; justice sociale; pol5185; premier cycle; périodes historiques; québec; ressource en ligne; régions géographiques; science politique; science politique et droit; sexisme; systèmes d'oppressions; thématiques